2014
DOI: 10.1177/1479164114539713
|View full text |Cite
|
Sign up to set email alerts
|

Haptoglobin genotype and cerebrovascular disease incidence in type 1 diabetes

Abstract: Objective We prospectively evaluated the Haptoglobin (Hp)-stroke association in type 1 diabetes and hypothesized that despite increasing the risk for coronary artery disease, the presence of the Hp 2 allele would lower stroke incidence. Methods Participants from the Epidemiology of Diabetes Complications study without prevalent stroke and Hp available were evaluated (n=607; mean age, 27.6 and duration, 19.3 years). Results During 22 years of follow-up, stroke incidence did not differ by Hp genotype (p=0.49… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 41 publications
1
27
2
Order By: Relevance
“…To evaluate the association between the HP genotype and cardio-renal mortality risk, deaths from causes other than cardiovascular or renal were treated as competing events. Although prior evidence suggested an inverse HP 2-2 – stroke association (14), six of the seven stroke deaths occurred among HP 2-2 carriers in this population and, therefore, stroke was not isolated from other cardiovascular causes of death. To analyze these competing risks data, procedure PHREG was used to model the cumulative incidence function, by defining the sub-distribution hazard according to a method developed by Fine and Gray (26).…”
Section: Methodscontrasting
confidence: 58%
See 1 more Smart Citation
“…To evaluate the association between the HP genotype and cardio-renal mortality risk, deaths from causes other than cardiovascular or renal were treated as competing events. Although prior evidence suggested an inverse HP 2-2 – stroke association (14), six of the seven stroke deaths occurred among HP 2-2 carriers in this population and, therefore, stroke was not isolated from other cardiovascular causes of death. To analyze these competing risks data, procedure PHREG was used to model the cumulative incidence function, by defining the sub-distribution hazard according to a method developed by Fine and Gray (26).…”
Section: Methodscontrasting
confidence: 58%
“…Our finding in the Epidemiology of Diabetes Complications (EDC) study of increased susceptibility to coronary artery disease (CAD) conferred by the HP 2 allele (11) has yet to be validated in other prospective cohorts, although a similarly increased risk was observed for the incidence of coronary artery calcification in the Coronary Artery Calcification in Type 1 Diabetes (CACTI) study (12). Despite the abundance of data rendering HP 2 as a risk factor for CAD, other EDC findings suggest a protective role for this allele against the extent of white matter hyperintensities (13) and stroke incidence (14). This contrasting finding may be mediated by the HP 2 allele’s enhanced angiogenic activity (1).…”
Section: Introductionmentioning
confidence: 99%
“…The Hp 1-1 genotype is also associated with development of stroke in Type 1 diabetes. 33 Metabolic Factors Related to Cerebral Small Vessel Disease A number of metabolic biomarkers have been studied in small caliber vascular disease in the brain, including individuals with diabetes mellitus, dyslipidemia, homocystinemia, and the metabolic syndrome. A strong association between metabolic syndrome and the presence of subcortical (OR = 1.99; 95% CI, 1.28-3.10; P = 0.002) and periventricular WMH lesions (OR = 2.23, 95% CI, 1.09-4.58; P = 0.03) was observed in a cross-sectional study in 1,151 healthy older Japanese subjects.…”
Section: White Matter Hyperintensity Lesions and Functional Declinementioning
confidence: 99%
“…For example, the Bruneck study included participants with prevalent disease at baseline and had a small number of cases during the 15 years of follow-up (123 cases, among which only 48 cases were CHD). The endpoint of CHD was combined with stroke, an endpoint which has been associated with the Hp1-1 genotype rather than Hp2-2 (14,15). It has been suggested that the protection conferred by the Hp1-1 genotype against CHD development is connected to function of Hp as the scavenger of free hemoglobin, while the role of Hp in angiogenesis may confer the protection against stroke associated with the Hp2-2 phenotype (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent analysis of cardiovascular disease among adults in the Bruneck study did not observe a similar association (13). The discrepancy may be due to several study design factors, especially the combined endpoint of CHD and stroke (the majority of cases were stroke), since stroke has been associated with the Hp1-1 genotype rather than the Hp2-2 genotype (14,15). However, the Bruneck study is of interest because it contained repeated measures of HbA 1c and provides suggestive evidence for a potential time-dependent bias against the Hp2-2 genotype as participants aged that supports previous findings of increased longevity among individuals with the Hp1-1 genotype (16,17).…”
Section: Introductionmentioning
confidence: 99%